Use of eGovernment in Public Services Area (Case Study: Bojonegoro Regency) - Hastie Audytra; Rahmat Irsyada (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
The objective of e-Government is the availability of access to information by the citizen rather than financial benefits. e-Government system is built based on web technology to provide better public services to the citizen. Public services are services provided by the government to the citizen. Bojonegoro itself has several times received awards in the field of Smart City or e-Government. In this study, we want to know how to apply digital government or e-Government in Bojonegoro Regency in the implementation of public services. From the results of the literature study and data collection from 250 public service users, it appears that the applications that are widely used or that attract public interest are national applications that have been around for a long time, such as the Lapor! And online tax service application. Local applications that are being actively socialized actually get the smallest percentage. This study provides recommendations for solutions that can be applied for the implementation of better public services.